2019
DOI: 10.1080/00380768.2019.1705181
|View full text |Cite
|
Sign up to set email alerts
|

Change in soil microbial biomass and regulating factors in an alpine meadow site on the Qinghai-Tibetan Plateau

Abstract: The change in soil microbial biomass (SMB) content and its direct links to soil organic matter (SOM) and environmental factors are not well understood for high-elevation regions. Therefore, this research investigated the temporal variation of SMB and its relationship with SOM and environmental factors in an alpine meadow site on the Qinghai-Tibetan Plateau. The soil organic carbon (SOC) and total nitrogen (TN) contents in alpine meadows showed monthly and seasonal variations and were higher in colder months, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 109 publications
2
4
0
2
Order By: Relevance
“…ecological parameters), of farming practices through farming intensity, land use and crop rotation, but also the previous effects of farming practices and soil microbial characteristics. Soil resources (SOC, TN and water stress) and soil habitat (clay and silt contents) had significant direct positive effects on SMMB, in agreement with other studies [12,13,[70][71][72][73]. This positive effect of soil properties may be related to their slight increase/decrease, as SOC or TN variations over long-term scales may lead to drastic changes in soil microbial communities [74,75].…”
Section: Plos Onesupporting
confidence: 88%
“…ecological parameters), of farming practices through farming intensity, land use and crop rotation, but also the previous effects of farming practices and soil microbial characteristics. Soil resources (SOC, TN and water stress) and soil habitat (clay and silt contents) had significant direct positive effects on SMMB, in agreement with other studies [12,13,[70][71][72][73]. This positive effect of soil properties may be related to their slight increase/decrease, as SOC or TN variations over long-term scales may lead to drastic changes in soil microbial communities [74,75].…”
Section: Plos Onesupporting
confidence: 88%
“…within the two years of the present study, the high sheep stocking density did not significantly reduce MBC due to the www.nature.com/scientificreports/ strong survival strategies of the Chinese grassland microbial communities. The turnover of microbial biomass is generally slow due to the extremely low temperatures in winter and long periods of drought in summer 49 , which allows a long survival under C limited conditions 45 . This slows down the microbial response to intensive sheep grazing of AGB.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the drought situation, increased precipitation was found to decrease MBC:MBN in water addition experiments [125], and field observation experiments similarly found that MBC:MBN decreased with increasing soil water contents [42]. The reasons for this may be the following: first, higher precipitation has a positive effect on bacterial biomass [126].…”
Section: Impacts Of Changing Precipitation Patternsmentioning
confidence: 94%